Corporate responsibility and sustainable development: a historical and conceptual view - Raufflet, Emmanuel (Cuadernos de Administración, 2010)
Over the last decade, the concepts of corporate responsibility and the notion of sustainable development have been widely disseminated both in the circles of both researchers and professionals in management. The purpose of this paper is to propose some elements of clarification with regard to these two concepts and in relation to the current context. This article includes three parts. First, it introduces a historical and conceptual evolution of the concept of corporate responsibility. Second, it maps an explanation of the current spread of this concept and identifies the linkages between dimensions of sustainable development and corporate responsibility. Finally, it proposes some ideas in relation to research on corporate responsibility in the specific context of Colombia